2018
DOI: 10.1002/evl3.58
|View full text |Cite
|
Sign up to set email alerts
|

Mutual fitness benefits arise during coevolution in a nematode-defensive microbe model

Abstract: Species interactions can shift along the parasitism‐mutualism continuum. However, the consequences of these transitions for coevolutionary interactions remain unclear. We experimentally coevolved a novel species interaction between Caenorhabditis elegans hosts and a mildly parasitic bacterium, Enterococcus faecalis, with host‐protective properties against virulent Staphylococcus aureus. Coinfections drove the evolutionary transition of the C. elegans–E. faecalis relationship toward a reciprocally beneficial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 56 publications
(61 reference statements)
3
65
0
Order By: Relevance
“…; Rafaluk‐Mohr et al. ). Thus, analyzing them in biologically relevant scenarios is a step forward toward understanding virulence evolution in the field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…; Rafaluk‐Mohr et al. ). Thus, analyzing them in biologically relevant scenarios is a step forward toward understanding virulence evolution in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, cross immunity, immunopathology, and spite can all lead to reductions in host exploitation rates, but this potential is only revealed in our asymmetric models. All of the interactions analyzed in this study have been found to take place in multi-parasite, asymmetric scenarios (Graham et al 2005;Ezenwa and Jolles 2011;Shrestha et al 2013;Rafaluk-Mohr et al 2018). Thus, analyzing them in biologically relevant scenarios is a step forward toward understanding virulence evolution in the field.…”
Section: Asymmetric Interactionsmentioning
confidence: 91%
See 2 more Smart Citations
“…This simple alteration of VVD's model-assumptions leads to a broad parameter space in which a stable population of helper microbes is maintained despite their costly behavior, suggesting selection at the holobiont-level (Fig 2). Such a non-linear dependency of fitness on an underlying factor that can be influenced by the microbiome is not uncommon in the real world, stemming from physiological, ecological, or behavioral factors (2)(3)(4)(5). VVD's model may thus suggest the opposite conclusion from the one they reach, depending on the choice of fitness function.…”
Section: Main Textmentioning
confidence: 99%